The Tale‐Tell Heart: Evolutionary tetrapod shift from aquatic to terrestrial life‐style reflected in heart changes in axolotl (Ambystoma mexicanum). Issue 6 (26th August 2021) - Olejnickova, Veronika; Kolesova, Hana; Bartos, Martin; Sedmera, David; Gregorovicova, Martina
Abstract: Background: During amphibian metamorphosis, the crucial moment lies in the rearrangement of the heart, reflecting the changes in circulatory demands. However, little is known about the exact shifts linked with this rearrangement. Here, we demonstrate such myocardial changes in axolotl ( Ambystoma mexicanum ) from the morphological and physiological point of view. Results: Micro‐CT and histological analysis showed changes in ventricular trabeculae organization, completion of the atrial septum and its connection to the atrioventricular valve. Based on Myosin Heavy Chain and Smooth Muscle Actin expression we distinguished metamorphosis‐induced changes in myocardial differentiation at the ventricular trabeculae and atrioventricular canal. Using optical mapping, faster speed of conduction through the atrioventricular canal was demonstrated in metamorphic animals. No differences between the groups were observed in the heart rates, ventricular activation times, and activation patterns. Conclusions: Transition from aquatic to terrestrial life‐style is reflected in the heart morphology and function. Rebuilding of the axolotl heart during metamorphosis was connected with reorganization of ventricular trabeculae, completion of the atrial septum and its connection to the atrioventricular valve, and acceleration of AV conduction. Key Findings: Rebuilding of the axolotl heart during metamorphosis was connected with re‐organization of ventricular trabeculae, completion of the atrial septum and its connection to the atrioventricular valve, and acceleration of AV conduction